PENGARUH KETERSEDIAAN DAN KAPASITAS JALAN TERHADAP PERMINTAAN KENDARAAN BERMOTOR DI KABUPATEN ENDE - Susu, Godifridus; Sedho, Yuliana (Program Studi Ekonomi Pembangunan Universitas Flores, 2021)
This study aims to determine the magnitude the influence of road availability and capacity on the demand for motorized vehicles in Ende Regency. The type of data used in this research is the form of an annual period which is quantitative data. With the Multiple Linear Regression analysis method which is tested partially and simultaneously. The results showed that the variable road availability and road capacity had a significant effect on the demand for motorized vehicles in Ende Regency. This is evidenced by the results of the F test, namely F count > F table (6,028> 2.79) so Ho is rejected, meaning that there is a real effect. While the t test results show that the variable road availability has no significant effect on the variable demand for motorized vehicles in Ende Regency, so Ho is accepted, but road capacity shows Ho is rejected, meaning that road capacity has a significant effect on demand for motorized vehicles in Ende Regency, this is evidenced by the results t count> t table (3.021>1,674)